Does sharing economy promote sustainable economic development and energy efficiency? Evidence from OECD countries - Amal Dabbous; Abbas Tarhini (Journal of Innovation & Knowledge (JIK), 2021)
The sharing economy is a new phenomenon considered to stimulate sustainable practices. It is viewed as the synergy between technology, information and marketing that promotes a new culture where customers favor access over ownership enabling them to use resources more efficiently. Therefore, it represents an innovative business model that can act as a potential pathway to sustainable economic development and energy efficiency. However, economic, and ecological impacts of the sharing economy remain controversial and need further investigation. In fact, sharing economy has disrupted the prevailing economic paradigm soliciting questions about the advantages and the risks of this new behavior. This study aims to fill this gap in the literature and quantitatively assesses the potential implications that the sharing economy has on sustainable economic development and energy efficiency. It builds a proxy indicator for the annual level of sharing economy use per country using internet search data from Google Trends. In addition, it uses annual secondary data for a balanced panel of 18 OECD countries for the period 2014-2018 to test the proposed models' hypotheses. The positive impacts of the sharing economy on sustainable economic development and energy efficiency are supported by the results of the fixed effect regressions with Driscoll-Kraay standard errors. The findings suggest that the sharing economy represents a socio-economic trend that has the potential to stimulate sustainable economic development and energy efficiency. Therefore, they highlight the power of the sharing economy and offer important theoretical and practical implications for researchers, individuals, and policy makers.
Keywords: 650; Energy efficiency; Sharing economy; Sustainable economic development